Membrane-Based Processes to Obtain High-Quality Water From Brewery Wastewater - Toran, Marc Sauchelli; Labrador, Patricia Fernández; Ciriza, Juan Francisco; Asensio, Yeray; Reigersman, André; Arevalo, Juan; Rogalla, Frank; Monsalvo, Victor M. (Frontiers in Chemical Engineering, 2021)
Water reuse is a safe and often the least energy-intensive method of providing water from non-conventional sources in water stressed regions. Recent advances in membrane technology allow for reclamation of wastewater through the production of high-quality treated water, including potable reuse. This study takes an in-depth evaluation of a combination of membrane-based tertiary processes for its application in reuse of brewery wastewater, and is one of the few studies that evaluates long-term membrane performance at the pilot-scale. Two different advanced tertiary treatment trains were tested with secondary wastewater from a brewery wastewater treatment plant (WWTP): A) ultrafiltration (UF) and reverse osmosis (RO), and B) ozonation, coagulation, microfiltration with ceramic membranes (MF) and RO. Three specific criteria were used for membrane comparison: 1) pilot plant optimisation to identify ideal operating conditions, 2) Clean-In-Place (CIP) procedures to restore permeability, and 3) final water quality obtained. Both UF and MF membranes were operated at increasing fluxes, filtration intervals and alternating phases of backwash (BW) and chemical-enhanced backwash (CEB) to control fouling. Operation of polymeric UF membranes was optimized at a flux of 25-30 LMH with 15-20 min of filtration time to obtain longer production periods and avoid frequent CIP membrane cleaning procedures. Combination of ozone and coagulation with ceramic MF membranes resulted in high flux values up to 120 LMH with CEB:BW ratios of 1:4 to 1:10. Coagulation doses of 3-6 ppm were required to deal with the high concentrations of polyphenols (coagulation inhibitors) in the feed, but higher concentrations led to increasing fouling resistance of the MF membrane. Varying the ozone concentration stepwise from 0 to 25 mg/L had no noticeable effect on coagulation. The most effective cleaning strategy was found to be a combination of 2000 mg/L NaOCl followed by 5% HCl which enabled to recover permeability up to 400 LMH·bar-1. Both polymeric UF and ceramic MF membranes produced effluents that fulfil the limits of the national regulatory framework for reuse in industrial services (RD 1620/2007). Coupling to the RO units in both tertiary trains led to further water polishing and an improved treated water quality.